Present status of the positive space charge lense for focusing intense negative charged particle beams - Goncharov, A.A.; Dobrovolskiy, A.M.; Dunets, S.M.; Litovko, I.V.; Gushenets, V.I.; Oks, E.M.; Bugaev, A.S. (Вопросы атомной науки и техники, 2012)
We describe the new experimental and simulation results of wide-aperture (6 cm) non-relativistic (up to 18 keV) intense (up to 400 mA) electron beam focusing by the positive-space-charge plasma lens. Recently we proposed and explored a new original plasma-optical tool for negative charged particle beams focusing and manipulating with a dynamic cloud of non-magnetized free positive ions and magnetically isolated electrons produced by a toroidal plasma source like an anode layer thruster. In such kind systems the electrons are separated from ions by relatively strong magnetic field in the discharge channel. The accelerated ions are weakly affected by the magnetic field owing to their mass. Focusing of the electron beam by electrostatic plasma lens was separated from magnetic focusing experimentally and the compression factor was up to about 5. The results of the computer simulation are shown good agreement with experimental data. Obtained experimental results demonstrate the possibility to create a lowcost high-effective tool for negatively-charged particle beam focusing without influence of momentum aberrations.